2011
DOI: 10.1002/clen.201000478
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Correlations and Variations of Air Pollutant Concentrations under Conditions of Rapid Industrialization – Kocaeli (1987–2009)

Abstract: In this study, it was aimed to characterize temporal variations of air pollutants for determining contribution to pollution episodes and to obtain correlations between these pollutants. With this aim we used data analysis for measured sulfur dioxide (SO 2 ), particulate matter (PM, black fume and PM10), nitrogen oxides (NO x ), ozone (O 3 ), carbon monoxide (CO), methane (CH 4 ), and non-methane hydrocarbons (NMHC) recorded in Kocaeli, one of the most industrilizated cities of Turkey. Pollutant concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…SO 2 and NO x are two of the main air pollutants generated by combustion processes, and both have harmful effects on human health. Moreover, it was proven that both pollutants are correlated [46], which is consistent with the model in (1). Fortunately, pollution episodes are not very frequent and the trend is that they will become scarcer as technology advances.…”
Section: Estimation Algorithmsupporting
confidence: 85%
“…SO 2 and NO x are two of the main air pollutants generated by combustion processes, and both have harmful effects on human health. Moreover, it was proven that both pollutants are correlated [46], which is consistent with the model in (1). Fortunately, pollution episodes are not very frequent and the trend is that they will become scarcer as technology advances.…”
Section: Estimation Algorithmsupporting
confidence: 85%
“…These correlations are also statistically significant. As we expect, sulphur dioxide and carbon monoxide correlate directly with PM10, considering that there are chemical processes that relate them (Doğruparmak and Özbay, 2011;Sharma and Sharma, 2016).…”
Section: Air Qualitymentioning
confidence: 81%
“…Specifically, sometimes pollution concentration can be high due to transported pollution produced elsewhere in the region. Various studies have been reported in the literature to investigate the correlation between different ambient air pollutants [57], [58].…”
Section: A Data Descriptionmentioning
confidence: 99%